2014
DOI: 10.1016/j.ijsu.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of gastrointestinal stromal tumours (GIST) and malignant neoplasms of different origin: Prognostic implications

Abstract: Coexistence of GIST with other malignancies is higher than previously reported and should draw attention of clinicians towards these incidental findings. Prognosis in these patients is usually determined by other malignancy and not significantly influenced by GIST. Therefore treatment algorithms should be focused on prognostically relevant malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 58 publications
5
47
0
1
Order By: Relevance
“…The largest study including 783 patients of one institutional tumor registry reported a rate of secondary neoplasms in 20% [22] . In contrast, very recently 43% of secondary neoplasms have been reported of a GIST cohort including only 86 patients [26] . Systematic work is missing regarding patient outcome and the assessment of overall survival (OS), disease specific survival (DSS) and disease free survival.…”
Section: Introductionmentioning
confidence: 93%
“…The largest study including 783 patients of one institutional tumor registry reported a rate of secondary neoplasms in 20% [22] . In contrast, very recently 43% of secondary neoplasms have been reported of a GIST cohort including only 86 patients [26] . Systematic work is missing regarding patient outcome and the assessment of overall survival (OS), disease specific survival (DSS) and disease free survival.…”
Section: Introductionmentioning
confidence: 93%
“…While the majority of these tumors are thought to arise spontaneously, approximately 5% are considered hereditary . There are multiple single institution and population based studies that have shown GIST patients to have an increased risk of developing additional malignancies, including renal cell carcinoma . Similar to GISTs, a minor proportion (5‐8%) of RCCs are known to occur due to hereditary etiology, and some with an identifiable genetic abnormality .…”
Section: Introductionmentioning
confidence: 99%
“…2019; 21(10):e90287. two other malignancies in addition to GIST (14). In 2010, studying the survival ratio of 783 GIST patients showed that 24 of them (3.1%) had had more than two other primary malignancies (15).…”
Section: Discussionmentioning
confidence: 99%